Factor VIII-Fc Activates Natural Killer Cells via Fc-Mediated Interactions With CD16 - Lagassé, H.A. Daniel; Hopkins, Louis B.; Jankowski, Wojciech; Jacquemin, Marc G.; Sauna, Zuben E.; Golding, Basil (Frontiers in Immunology, 2021)
The most challenging complication associated with Factor VIII (FVIII) replacement therapy is the development of neutralizing anti-drug antibodies, or inhibitors, which occur in 23-35% of severe (FVIII level <1%) hemophilia A (HA) patients and are a serious hindrance to effective management of HA. Consequently, strategies that can either prevent anti-FVIII inhibitors from developing or “tolerize” individuals who develop such antibodies represent a clinically important unmet need. One intervention for patients with high-titer inhibitors is immune tolerance induction (ITI) therapy. Although ITI therapy is the only clinically proven strategy to eradicate anti-FVIII inhibitors, mechanisms of inhibitor reduction remain unknown. Factor VIII Fc-fusion (rFVIIIFc) is an enhanced half-life antihemophilic factor used in replacement therapy for HA. Fc-fusion is a successful protein bio-engineering platform technology. In addition to enhancement of plasma half-life via neonatal Fc receptor (FcRn) binding, other Fc-mediated interactions, including engagement with Fc gamma receptors (FcγR), may have immunological consequences. Several case reports and retrospective analyses suggest that rFVIIIFc offers superior outcomes with respect to ITI compared to other FVIII products. Previously we and others demonstrated rFVIIIFc interactions with activating FcγRIIIA/CD16. Here, we investigated if rFVIIIFc activates natural killer (NK) cells via CD16. We demonstrated rFVIIIFc signaling via CD16 independent of Von Willebrand Factor (VWF):FVIII complex formation. We established that rFVIIIFc potently activated NK cells in a CD16-dependent fashion resulting in IFNγ secretion and cytolytic perforin and granzyme B release. We also demonstrated an association between rFVIIIFc-mediated NK cell IFNγ secretion levels and the high-affinity (158V) CD16 genotype. Furthermore, we show that rFVIIIFc-activated CD16+ NK cells were able to lyse a B-cell clone (BO2C11) bearing an anti-FVIII B-cell receptor in an antibody-dependent cellular cytotoxicity (ADCC) assay. These in vitro findings provide an underlying molecular mechanism that may help explain clinical case reports and retrospective studies suggesting rFVIIIFc may be more effective in tolerizing HA patients with anti-FVIII inhibitors compared to FVIII not linked to Fc. Our in vitro findings suggest a potential use of Fc-fusion proteins acting via NK cells to target antigen-specific B-cells, in the management of unwanted immune responses directed against immunogenic self-antigens or therapeutic protein products.